Pengaruh Influencer Marketing, Online Customer Review dan Online Customer Rating terhadap Minat Beli Produk Skincare di Shopee pada Generasi Z di Kecamatan Kisaran Timur Kabupaten Asahan - Della Ayu Yolanda; Surya Bakti (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The rapid growth of e-commerce has significantly changed consumer purchasing behavior, particularly among Generation Z. One of the most popular platforms in Indonesia is Shopee, where skincare products are widely purchased. This study aims to analyze the influence of Influencer Marketing, Online Customer Reviews, and Online Customer Ratings on Purchase Intention of skincare products on Shopee among Generation Z in Kisaran Timur District, Asahan Regency. This research employs a quantitative approach with an associative research method. The sample consisted of 96 respondents selected using accidental sampling technique. Data were collected through questionnaires using a Likert scale. The data were processed using SPSS version 25 and analyzed using multiple linear regression analysis. The results show that Influencer Marketing, Online Customer Reviews, and Online Customer Ratings simultaneously and partially have a significant positive effect on purchase intention. Influencer Marketing is the most dominant variable influencing consumer decisions. The coefficient of determination indicates that these three variables explain a substantial proportion of variation in purchase intention, while the remaining influence is determined by other factors outside this study. In conclusion, social media-based marketing strategies and user-generated content play an important role in shaping consumer buying interest in the digital marketplace among Generation Z.